S. aureus drives itch and scratch-induced skin damage through a V8 protease-PAR1 axis - Deng, Liwen; Costa, Flavia; Blake, Kimbria J; Choi, Samantha; Chandrabalan, Arundhasa; Yousuf, Muhammad Saad; Shiers, Stephanie; Dubreuil, Daniel; Vega-Mendoza, Daniela; Rolland, Corinne; Deraison, Celine; Voisin, Tiphaine; et al. (Cell, 2023)
Itch is an unpleasant sensation that evokes a desire to scratch. The skin barrier is constantly exposed to microbes and their products. However, the role of microbes in itch generation is unknown. Here, we show that Staphylococcus aureus, a bacterial pathogen associated with itchy skin diseases, directly activates pruriceptor sensory neurons to drive itch. Epicutaneous S. aureus exposure causes robust itch and scratch-induced damage. By testing multiple isogenic bacterial mutants for virulence factors, we identify the S. aureus serine protease V8 as a critical mediator in evoking spontaneous itch and alloknesis. V8 cleaves proteinase-activated receptor 1 (PAR1) on mouse and human sensory neurons. Targeting PAR1 through genetic deficiency, small interfering RNA (siRNA) knockdown, or pharmacological blockade decreases itch and skin damage caused by V8 and S. aureus exposure. Thus, we identify a mechanism of action for a pruritogenic bacterial factor and demonstrate the potential of inhibiting V8-PAR1 signaling to treat itch.